ANALISIS PENERAPAN BUNGA PINJAMAN DENGAN METODE SLIDING RATE DANFLAT RATE PADA KOPERASI KREDIT GENTIARAS PRINGSEWU - Felix Alfa Yudhistira; Yohanes Suharsana (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2020)
Kopdit Gentiaras Pringsewu doing giving flowers with Sliding rate method. Sliding rate method is a method of charging interest each month is calculated from the remainder of the loan so the interest paid members monthly decreases with decreasing principal. In order to compete with other cooperatives in other cooperative Pringsewu in Pringsewu, Kopdit GENTIARAS set loan interest rate by a sliding method. However, these methods do not necessarily provide benefits to its members. This research uses case study research with descriptive approach. Analysis of the data used is quantitative analysis. Results from this study is the difference in interest grouping. Calculation method of sliding rate is 1.75% x the remainder of the principal while the flat rate is 1.75% x the loan early.The results of this study provide the conclusion that the method of sliding rate is more beneficial to the members who make loans in Kopdit Gentiaras Pringsewu. Because by using this method the loan interest will always decreases with decreasing remainder of the loan.